Emotion expression in post-MI/PCI patients : the effects of two types of social sharing on psychological and physiological outcomes - Wilczkiewicz, Ewa (Trinity College (Dublin, Ireland). School of Psychology, 2016)
Cardiovascular Disease (CVD) is currently the world’s major cause of death, killing 17 million people a year (World Health Organisation; WHO, 2011). In Ireland 10,000 people die each year from CVD (33% of all deaths), half of whom die due to a heart attack (Irish Heart Foundation, 2012). Numerous demographic, clinical and behavioural characteristics have been associated with the higher risk of development of CVD and recovery from cardiac events, including psychological distress (e.g., depression, anxiety), negative emotions (e.g., anger) and emotion inhibition (e.g., Type D personality, anger suppression). Brief interventions inducing the expression of emotions have been tested for over 25 years; some have proved effective (expressive writing paradigm), while the procedure of others (social sharing) is still being improved. In this study, social sharing of facts and emotions was compared to natural social sharing, without an added instruction for emotion expression. Outcomes examined are psychological distress and affect, as well as blood pressure and heart rate. Additionally, heart rate variability is recorded during sharing interviews. The study also investigates possible moderating effects of Type D personality and Alexithymia, and mediating effects of emotion regulation. Chapter 1 introduces the concept of emotion inhibition and its deleterious effects on health and wellbeing, and outlines emotion regulations theories, highlighting emotion inhibition-related regulation strategies. The chapter concludes that whereas the act of emotion inhibition may initially serve adaptive goals, when it is applied continuously, as a trait or coping style, is leads to adverse outcomes on psychological and physical health. Chapter 2 discusses emotion expression in general, as well as interventions designed to induce emotion expression, such as the writing task, and outlines their effects (positive and negative) on various outcomes. This chapter concludes that, in general, written expression is a promising method of improving psychological and physical health both through catharsis and cognitive processing of a negative experience. Chapter 3 introduces the concepts of social sharing and verbal emotion expression. First, the chapter defines social sharing, discusses initial retrospective/diary studies, as well as subsequent laboratory studies. Second, it introduces verbal emotion expression and its effects. The chapter concludes that although natural social sharing has no apparent benefits, a social sharing intervention with induced emotion expression has not been thoroughly studied. Chapter 4 outlines Coronary Heart Disease, its aetiology, treatment and risk factors. In particular, psychological factors are discussed, as well as psychological treatments offered to cardiac patients. Chapter 5 presents the study rationale and the main model, as well as the results of the feasibility study that was conducted to test the study procedure, before implementing it with a clinical sample. Results suggested the procedure was understandable for participants, easy to follow, and safe, as it did not generate distress. Chapter 6 outlines the main study hypotheses, and main study procedure including results of reliability analysis for all the scales used. Chapters 7 and 8 present the results. Although for general post-MI sample the intervention did not bring expected effects on distress, a positive impact on physiology was observed. Furthermore, the intervention had some potential benefits for Type D individuals (mediated by rumination change) and people with Alexithymia. Chapter 9 presents qualitative analysis of participants’ narratives. Chapter 10 discusses the study findings and concludes with an outline of main implications for theory and research, such as the necessity of focusing social sharing interventions on Type D individuals, as well as post-MI care.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin